The problem of perfectionism and personality maturity in terms of ecological education - M. V. Kostsova; A. G. Mikhaylova; A. V. Grishina (Вестник Северо-Кавказского федерального университета)
Introduction. The phenomenon of personal maturity is multidimensional. It plays an important role in human consciousness and, therefore, the effectiveness of environmental education depends on it. In these conditions, the task of strengthening the ecological orientation of education and finding effective ways to form an ecologically concerned culture and a responsible attitude of people towards the ecological issues and eco-friendly processes is becoming more urgent. The study focuses upon a problem of perfectionism and personality maturity in the context of ecological education.Goal. To identify significant correlations between reflexivity and self-efficacy of students it is necessary to conduct a theoretical analysis of the problem of personality maturity, and identify the relationship between personality maturity and perfectionism in the context of empirical research.Materials and methods. Hewitt-Flett Multidimensional Perfectionism Scale; Differential test of perfectionism by A. A. Zolotareva and methods of mathematical statistics.Results and discussion. The results of A. Zolotareva method aimed at identifying perfectionism among future specialists show that the majority of subjects have a normal type of perfectionism, that is, such students are characterized by an individual’s desire for perfection, the ability to increase self-esteem based on achievements, success, experiencing slight excitement, excitement, easy entry into activities, focusing on one’s own resources, self-confidence. According to the questionnaire by P. Hewitt and G. Flett, the indicator for assessing selfefficacy of subject activity is within the range of average values. These subjects evaluate the results of their activities according to the situational context. They also see certain shortcomings in their activities and their results. It is clear that the formation of personality maturity as a psychological phenomenon can help overcome the environmental crisis.Conclusion. The authors came to the conclusion that there was a relationship between the personal maturity and perfectionism of students, namely, a negative relationship was identified between the components of perfectionism and personal maturity. Thus, there are significant correlations between students’ reflexivity and self-efficacy.